Effects of fibrin adhesive material (Tissucol) on alveolar healing in rats under stress. - Alves-Rezende, Maria C. R. [UNESP]; Okamoto, Tetuo [UNESP] (My University, 1997)
The effects of Tissucol on alveolar healing following stress were evaluated histologically, comparing three groups of 28 male albino rats each. Stress was applied and their right upper incisors were extracted. Group A served as an empty control site. In Group B, Tissucol was applied into the alveolar cavity. Group C received local antifibrinolytic treatment (alveolar irrigation with epsilon-aminocaproic acid solution) before implant of Tissucol into the tooth socket. Four animals in each group were killed at 1, 3, 6, 9, 15, 21 and 24 days after surgery. Results showed that: 1) Tissucol did not interfere with connective and osseous tissue formation; 2) Tissucol allowed new bone formation; 3) Tissucol residues in Group B in sections of 24-day specimens did not impair healing; 4) Tissucol was usually completely resorbed and healing was complete 24 days after surgery in Group C.
Keywords: fibrin glue; tissue adhesive; animal; comparative study; drug effect; exercise; incisor; jaw; male; maxilla; pathophysiology; rat; stress; time; tooth extraction; Wistar rat; wound healing; Alveolar Process; Animals; Fibrin Tissue Adhesive; Incisor; Male; Maxilla; Rats; Rats, Wistar; Restraint, Physical; Stress; Time Factors; Tissue Adhesives; Tooth Extraction; Wound Healing